Physical Therapy to Prevent Osteopenia in Preterm Infants: A Systematic Review - Galaad Torró-Ferrero; Francisco Javier Fernández-Rego; Antonia Gómez-Conesa (MDPI AG, 2021)
Background: During the last trimester of pregnancy, about 80% of the infant's calcium is incorporated, and for this reason, preterm infants have less bone mineralization compared to those born at term. The aim of the present systematic review was to identify, evaluate and summarize the studies that deal with the effect of physiotherapy modalities in the prevention and treatment of osteopenia in preterm infants. Methods: A comprehensive search (09/2019-02/2021) using PubMed, Web of Science, SCOPUS, ProQuest, SciELO, Latindex, ScienceDirect, PEDro and ClinicalTrials.gov was carried out. The following data were extracted: The number of participants, characteristics of the participants, design, characteristics of the intervention, outcome measures, time of evaluation and results. A non-quantitative synthesis of the extracted data was performed. The methodological quality and risk of bias were assessed using a PEDro scale and ROB-2 scale, respectively. Results: A total of 16 studies were analyzed, presenting a methodological quality that ranged from 3 to 8 points, and all showed some concerns regarding their risk of bias. Almost all studies (15/16) used passive mobilizations with joint pressure to prevent osteopenia, but they differed in the intensity and frequency of application. Conclusions: A daily exercise program of passive mobilizations with joint pressure, improves bone mineralization in preterm infants admitted to neonatal units.